2011
DOI: 10.1007/s00167-011-1591-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical repair of the distal biceps brachii tendon: a comparative study of three surgical fixation techniques

Abstract: In summary, we achieved good clinical and functional results after surgical repair of the distal biceps tendon using Corkscrews, Mitek anchors, or transosseous sutures. The results conferred by Corkscrews were comparable to the other techniques, justifying their use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…Several surgical options have been described in literature: one incision-approach, using suture anchors, endobutton, biotenodesis screw for fixation, and a double-incision approach, using bone tunnels [8, 15, 19, 21, 22]. Standard and modified double incision approach differ one to each other in ulnar periosteum exposure, avoided by the Morrey’s muscle-splitting technique that reduces risk of synostosis [23, 24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several surgical options have been described in literature: one incision-approach, using suture anchors, endobutton, biotenodesis screw for fixation, and a double-incision approach, using bone tunnels [8, 15, 19, 21, 22]. Standard and modified double incision approach differ one to each other in ulnar periosteum exposure, avoided by the Morrey’s muscle-splitting technique that reduces risk of synostosis [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…No statistically significant differences among groups were observed relative to ROM recovery rate. While no adverse events were described for the double-incision group, LACBN injury was reported in 5 cases in the single-incision cohort of patients [22]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical repair is performed with use of either a one-incision approach, originally described by Dobbie 3 , or a two-incision approach, described by Boyd and Anderson 4 . Multiple fixation methods have been developed, including bone tunnels [5][6][7][8][9][10][11][12][13][14][15][16] , suture anchors 2,5,7,9,11,15,[17][18][19][20][21][22] , intraosseous (biotenodesis) screws 5,16,23 , and suspensory cortical buttons 16,[24][25][26][27][28] . The complications of this procedure include lateral antebrachial cutaneous nerve injury, radial sensory nerve injury, superficial infection, deep infection, heterotopic ossification, posterior interosseous nerve palsy, radioulnar synostosis, limited elbow motion, and tendon rerupture 29 .…”
mentioning
confidence: 99%
“…Cadaveric studies have suggested that the PIN can be incarcerated by the cortical button or drill with drilling at 45 degrees distally or radially, with the mean distance nearing 2 mm. This can be improved by ulna and perpendicular drill hole placement to 11 mm [29][30][31][32][33][34]. This is a small cohort of patients with ADBR undergoing fixation with this dual technique with a 12% loss to follow up rate.…”
Section: Figure 2 Table Of Comparative Studies Of Re-rupture Rate Andmentioning
confidence: 99%